Visual narratives of global politics in the digital age: an introduction. Issue 5 (9th September 2020) - Crilley, Rhys; Manor, Ilan; Bjola, Corneliu
Abstract: Social media are inherently visual platforms. Every day, billions of photographs, videos, cartoons, memes, gifs, and infographics are uploaded and shared for the world to see online. As a result, political actors such as diplomats, militaries, international organisations, terrorist groups, corporations, celebrities, diasporas and members of the general public are now visual narrators of global politics. They tell stories about themselves, each other, and the rest of the world through the images they share on social media. Consequently, it is imperative that scholars of International Relations analyse visual narratives of global politics in the digital age. This article introduces the special issue on this topic by drawing together and advancing research on narratives, visual global politics, and digital media. In doing so we outline the conceptual underpinnings of, and rationale for, the special issue before introducing the contributions of each of the articles collected herein.